The qTSN4 Effect on Flag Leaf Size, Photosynthesis and Panicle Size, Benefits to Plant Grain Production in Rice, Depending on Light Availability - Fabre, Denis; Adriani, Dewi E.; Dingkuhn, Michael; Ishimaru, Tsutomu; Punzalan, Bermenito; Lafarge, Tanguy; Clément-Vidal, Anne; Luquet, Delphine (Frontiers in Plant Science, 2016)
Increasing rice yield potential is essential to secure world food supply. The quantitative trait locus qTSN4 was reported to achieve yield increases by enhancing both source and sink capacity. Three greenhouse experiments and one field experiment in the Philippines were conducted to study near-isogenic lines (NIL) in two genetic backgrounds, subjected to treatments with restricted light resources through shading (greenhouse) or population density (field and greenhouse). A consistent promotion of flag leaf width, leaf area and panicle size in terms of spikelet number was observed in the presence of qTSN4, regardless of environment. However, grain production per plant was enhanced only in one greenhouse experiment. An in-depth study demonstrated that increased flag leaf size in the presence of qTSN4 was associated with increased photosynthetic rates, along with lower SLA and greater N content per leaf weight and per area. This was emphasized under low light situation as the qTSN4-NILs did not express shade acclimation traits in contrast with the recipient varieties. The authors conclude that qTSN4 is a promising subject for further physiological studies, particularly under limited radiation. However, the QTL alone may not be a reliable source of increased yield potential because its effects at the plant and population scale are prone to genotype X environment interactions and the increased panicle size is compensated by the adaptive plasticity of other morphological traits.